The Effect Of Copy Writing In Bilboard Advertising Against Adolescent Smoking Behavior In Tengahtani Village, Cirebon District - Khodijah, Tiara; Daud, Rosy Febriani (ARRUS Journal of Social Sciences and Humanities, 2025)
In Indonesia, smoking behavior among teenagers is a health problem that still needs attention. The prevalence of adolescent active smokers in Indonesia was recorded at 22.04% in 2022. The problem of the risk of disease due to smoking does not only occur in active smokers but also in passive smokers. There are 57.8% of teenagers exposed to cigarette smoke at home and 67.2% exposed to cigarette smoke in open public places. This happens a lot because of cigarette advertisements that are everywhere. Likewise, smoking behavior among teenagers in Tengahtani village cannot be separated from social media, one of which is billboards that can be used by the cigarette industry to market cigarette products. Parents can report smoking to teenagers aged 18-24 years. This research aims to determine the impact of beerboard advertising media on the knowledge, attitudes and actions of Tengahtani teenagers. This type of research is quantitative which uses data and data sources. The impact of Billboard advertising media has a big influence on Tengahtani teenagers. To prevent this, namely by tightening the rules on cigarette advertising, one of which is Billboard advertising which can have an impact on the behavior of teenagers in Tengahtani village, namely limiting cigarette advertising, promotion and sponsorship